353 Amlitelimab reduces serum IL-13 in a phase 2a clinical trial in atopic dermatitis without impacting T-cell expansion in a T-cell recall assay. (25th January 2023) - Weidinger, Stephan; Cork, Michael; Reich, Adam; Bieber, Thomas; Lucchesi, Davide; Rynkiewicz, Natalie; Sainson, Richard C A; Chen, Ron; Prandi, Francesca; van Krinks, Cassandra; Stebegg, Marisa; Porter-Brown, Ben
Abstract: Amlitelimab (SAR445229), a fully human non-depleting, non-cytotoxic, monoclonal antibody, binds to OX40Ligand (OX40L) on antigen-presenting cells (APC) to block OX40-OX40L interactions. In a 16-week, double-blind, Phase 2a trial (NCT03754309), amlitelimab induced clinically meaningful disease activity improvement in patients with moderate-to-severe atopic dermatitis (AD). To assess the effects of amlitelimab on interleukin (IL)-13 and T-cell recall responses. In the trial, 89 patients were randomized to amlitelimab low dose (LD; 200 mg loading/100 mg maintenance every 4 weeks [Q4W]), high dose (HD; 500 mg loading/250 mg maintenance Q4W), or placebo. Serum IL-13 levels were assessed by single molecule immunoassay (259 samples). Using human peripheral blood mononuclear cells from five healthy donors, a T-cell recall assay was performed. At baseline in the trial, IL-13 levels significantly correlated with disease severity (Eczema Area and Severity Index; r = 0.4784, P < 0.0001). Week 16 IL-13 levels were significantly reduced with amlitelimab vs. baseline but not placebo (median fold change [95% confidence interval, CI] from baseline to week 16 with P -values based on two-way Analysis of Variance [ANOVA] of log10-transformed fold change for patients with a complete dataset at week 16: LD 0.345 [0.23–0.44], P < 0.0001; HD 0.390 [0.30–0.63], P = 0.0002; placebo 0.835 [0.34–1.12], P = 0.1544). In a T-cell recall assay, amlitelimab significantly reduced IL-13 protein levels at days 3 and 6 without negatively impacting T-cell expansion, based on the percentage of proliferating CD4 + T-cells vs. isotype control. Amlitelimab decreased IL-13 levels in patients with AD and in a T-cell recall assay without negative effects on T-cell expansion, thus reducing inflammation without blocking T-cell proliferation during recall responses.